The Potential of Sharia Fintech in Increasing Micro Small and Medium Enterprises (MSMEs) in The Digital Era in Indonesia - Syarifuddin Syarifuddin; Rahmawati Muin; Akramunnas Akramunnas (JURNAL HUKUM EKONOMI SYARIAH, 2021)
The potential for financial technology development or fintech with sharia basis in Indonesia is still quite large. Indonesia as the largest Muslim country in the world, becomes an undeniable potential. The purpose of this research is to know the potential of Fintech in increasing MSMEs in the digital era in Indonesia. This study uses document studies with a literature review approach. The results of this research show that. First, The patterns applied by sharia fintech in dealing with the problems faced by MSMEs in Indonesia include the ability to manage and analyze data in the era of big data, improve technology infrastructure, create transaction systems easily, content-based marketing in terms of digital marketing, establish cooperation, collaboration, and investment with relevant stakeholders, and innovation of fintech products. Second, The potential of Sharia Fintech in increasing MSMEs in the digital era in Indonesia, MSMEs have been using many applications and cooperating with banks and sharia Savings and Loan Cooperatives, so as to provide easy access to various types of bank financial services and savings and loan cooperatives, now financial institutions are able to reach all MSMEs to remote areas, Sharia Fintech has opened access to business financing more easily and quickly from banking institutions and other Islamic financial institutions.